Transforming into A Digitally Prepared Academic Community: The Perfect Mediating Role of Perceived Usefulness - Tamalla Octabilla Nusyani; Widiya Dewi Anjaningrum; Alma Pia G. Reyes (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2024)
Digital transformation has drastically altered various aspects of life, particularly in the realm of education. So, the entire academic community must be prepared to address the current changes. This research seeks to ascertain the mediating role of perceived usefulness in the relationship between proactive personality and growth mindset on employee's digital readiness. The study's population included all lecturers and employees of Institut Teknologi dan Bisnis Asia Malang, amounting to 180 individuals. The respondents were selected using a disproportionate stratified random sampling procedure, with a total sample size of 124 individuals. The quantitative data gathered from the distribution of questionnaires were ultimately analyzed using SmartPLS 4.1.0.8 software. The study's findings indicated that while the employee is categorized as proactive and possesses a growth mindset, these traits alone do not enhance the employee's digital readiness. This is contingent upon the individual having a favorable perception of the usefulness of the digital technology. Employees need to take the initiative and adopt a mindset focused on growth to foster this positive perception. It is recommended to expand the scope of research to include participants from multiple campuses. This could provide a range of insights and perspectives, enhancing the robustness of the findings.